The UN Draft Declaration on the Rights of Indigenous People - The International and Constitutional Law Contexts - Quentin-Baxter, Alison (Victoria University of Wellington Law Review, 1999)
This article is an edited version of one of the six papers presented to the International Law Association/International Commission of Jurists seminar on the UN Draft Declaration on the Rights of Indigenous Peoples which was held in Wellington on 23 August 1997. The author discusses the New Zealand Government policy towards the Draft Declaration on the Rights of Indigenous Peoples. She first identifies key issues of international law, explores the relationship between the Draft Declaration and the Treaty of Waitangi, and looks at some implications of both for the New Zealand legal system and our national society. In doing so, the author focuses on the political rights of indigenous peoples – particularly the principles underlying those rights, not the way they are expressed in the text. The author concludes that most, if not all, the significant changes in the international community and in the lives of nations have been brought about by acts of good faith. Accordingly, it is the author’s belief that the end product is likely to be the strengthening of the national societies to which the indigenous peoples of the world belong.